Kuat Tekan dan Penyerapan Batako Menggunakan Serat Pelepah Kelapa - Darul Niham Wahono; Zaenuri Arifin; Yosef Cahyo Setianto Poernomo; Zendy Bima Mahardana; Ashabul Yamin (Faculty of Engineering, Kadiri University, 2021)
Brick is a building material that has a function as a room sealer. Its larger size, when compared to red brick, makes bricks more in demand in the market. Improving the quality of bricks needs to be done to meet the needs of the building. The use of added materials becomes one of the things that can be considered to improve the nature and quality of bricks. This research aims to find out the strong press and absorption of bricks with the use of coconut pellet fiber. The research was conducted experimentally with the manufacture of test objects in the laboratory. The test object used is in the form of a beam of 30x15x10 cm. The percentage variation of coconut fiber is 5%, 10%, and 15% of the weight mass in bricks. The tests carried out include a strong compressive and water absorption test with reference to the Indonesian National Standard (SNI). The results of water absorption tests obtained the optimum value in bricks with a mixture of 5% fiber which is 6% of the mass of the weight of the brick, while the minimum value is in the brick, 15% fiber, which is 10%. While the compressive strength results get the optimum value on the 5% fiber mix variation, which is 20.1 kg/cm², and the minimum value on the variation of 15% fiber is 8.8 kg/cm². From these results showed that bricks with coconut pellet fiber have not been able to improve the quality of bricks.